Transformation of Traditional Arts Performances as Cultural Tourism Attraction: Case Study of Saung Angklung Ujdo - ., Priyanto; Yuliyanto, H; Musthofa, B M (KnE Social Sciences, 2018)
In the current era of globalization, tradition arts performing needs the attention of various parties. It is related to the principle of preservation of cultural traditions, that is, the tradition arts performing should still be preserved. At the same time, globalization so powerfully grinds the tradition arts performing. One of the effects of globalization in the field of tourism was marked by the exploration of cultural tourism attractions including the tradition arts performing. The alternative solution to these problems is cultural adaptation (adaptation of tradition arts performances) in accordance with the demands of time, but without compromising the essence of it. This article aims to describe how the transformation of the traditional art performances at Saung Angklung Udjo presents as the attraction of cultural tourism that attracts tourists. A qualitative approach is used to analyze the topic through the performing observation and deep interview to get the information and data. The results showed that Saung Angklung Udjo has made changes to the tradition arts performing as being one of the attractions that attract cultural tourism by working on some of the components and the basic elements of the performance. Tradition arts performance at Saung Angklung Udjo is relatively simple, densely packed, entertaining, and interactive without losing the essence of the tradition arts performance. It is one of the alternative attractiveness of cultural tourism that supports the tourism industry. Keywords: tradition arts performance, cultural tourism, Angklung, Saung Ujo